The diagnosis and treatment of a special rare type of Monteggia equivalent fractures in children - Su, Fei; Li, Min; Ma, Yishan; Yang, Yating; Hao, Xue; Jia, Haoruo; Dang, Youting; Lu, Qingda; Liu, Chenxin; Yang, Shuai; Wang, Huan; Wang, Bing; et al. (Frontiers in Pediatrics, 2023)
Purpose: To explore the characteristics, mechanism, treatment, and prognosis of head-neck separation type of Monteggia equivalent fractures in children. Methods: The patients with this injury were reviewed retrospectively. The lesion was characterized by a fracture of the ulnar with radial neck fracture but without dislocation of the radial head. Our classification was based on the direction of displacement and angulation of fractures on radiographs, divided into the extension-valgus type and flexion-varus type. The fractures were treated with reduction and internal fixation, depending on the fracture type. The clinical results were evaluated by radiology and the Mayo Elbow Performance Score (MEPS). Results: 12 patients were followed up for an average of 40.5 months. The ulnar fractures were treated with closed reduction (CR) and K-wires fixation in 1 case, elastic stable intramedullary nail（ESIN） fixation in 4 cases, open reduction (OR), and plate fixation in 5 cases, with no fixation in 2 cases. CR with ESIN succeed in 11 cases of radial neck fractures, but one underwent OR and K-wires fixation. All fractures healed on time, with fewer complications (avascular necrosis in 1 case, bulk formation of metaphysis in 1 case). The therapeutic efficacy was evaluated by MEPS as excellent in 10 cases, good in 1 case, and fair in 1 case. Conclusions: The head-neck separation type of Monteggia equivalent fractures in children is rare. Its characteristics are different from Monteggia fracture. The length and anatomic structure of the ulna should be restored and stabilized first, while the radial neck fracture should be treated with CR and ESIN fixation. Satisfactory clinical results can be achieved with fewer complications.